Keterkaitan Antara Pengaruh Struktur Sosial dan Ekonomi Terhadap Kebijakan Redistribusi Pendapatan Studi Kasus Provinsi Kepulauan Riau - Aphira, Gery; Pangestoeti, Wahjoe; Syahrani, Andhini; M, Maharani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This article examines the relationship between social structure and economic structure on the implementation of income redistribution policies in the Riau Islands Province. The research method used is a descriptive analysis research method with a literature study approach. Based on the research results, it is known that there is a correlation or link between social structure and economic structure on income redistribution policies. Social structure and economic structure are able to represent community welfare and visualize income gaps. In this way, it is hoped that the social structure and economic structure can be used as an illustration regarding the targeting of income redistribution policies so that they are not mistargeted.